Study of Neutron From a Dense Plasma Focus Paco Instrument by Means of Nuclear Tracks Detectors - Milanese, Maria Magdalena (2016)
most interesting feature of dense plasma foci is the acceleration of charge particle at energy in the range of MeV per nucleon. Using deuterium gas, this devices produce fusion D-D reactions, generation fast neutron pulses (~ 2.5 MeV). The device used in the present work is a Mather-type dense plasma focus, called PACO. It is a 2kJ device at 31 kV, with an oxygen-free copper anode, 50 mm long with 40 mm diameter. The coaxial cathode is formed by ten copper rods arranged in a squirrel cage configuration at a radius of 50 mm. The insulator in an annular Pyrex ® tube located at the base of the anode. The energy store is provided by four 1 μF (40 kV, 40 nH) capacitors in parallel. The plasma focus was operated at 1.5 mb deuterium gas pressure. Neutron and accelerated particles are analyzed with material detectors (CR-39 Lantrack® ) for different conditions. A detailed study is made of track diameters when the plastic is chemically etched with, 6N KOH at 60°C (±1) for 12 h.